Ethnopharmacy and Traditional Knowledge Study with a Family Use Value Approach in Sumberbrantas Village, Bumiaji District, Batu City, East Java - Rosyid Ridho, Muhammad Ainur; Trisnawati, Indah; Nurhidayati, Tutik; Purwani, Kristanti Indah; Saptarini, Dian; Kuswytasari, Nengah Dwianita (RUMPHIUS, 2025)
Indonesia is recognized as one of the world’s most biodiverse countries, with an estimated 17% of global plant and animal species found within its borders. This biodiversity supports a wealth of medicinal plants that have been traditionally utilized by local communities. However, rapid modernization has led to a decline in the transmission of ethnobotanical knowledge. This study investigates the ethnopharmacological practices in Sumberbrantas Village, Bumiaji District, Batu City, East Java, with a focus on the Family Use Value (FUV) approach to identify the most utilized plant families in traditional medicine. Data were collected through structured interviews with 70 respondents selected using purposive and snowball sampling techniques. The study analyzed the FUV and Fidelity Level (FL) of various plant species to determine their significance in traditional healing practices. Results indicate that the Zingiberaceae and Euphorbiaceae families have the highest FUV (0.45), highlighting their widespread use in treating various ailments. Conversely, the Oxalidaceae family exhibits the lowest FUV (0.01). The FL analysis shows that Allium cepa (shallot) has the highest fidelity level (75%), demonstrating its prominence in treating multiple conditions. This research provides critical insights into the preservation of ethnomedicinal knowledge and the sustainable use of medicinal plant resources. The findings serve as a valuable reference for conservation efforts and the development of community-based herbal medicine initiatives.